The crystal structure of (2,7-dimethoxynaphthalene-1,8-diyl)bis((3-nitrophenyl)methanone), C26H18N2O8 - Li Kun; Iitsuka Hiroaki; Ohisa Shinji; Nishijima Takahiro; Noguchi Keiichi; Yonezawa Noriyuki; Okamoto Akiko (Zeitschrift für Kristallographie - New Crystal Structures)
C26H18N2O8, triclinic, P1̄ (no. 2), a = 8.41284(15) Å, b = 10.9410(2) Å, c = 12.9659(2) Å, α = 114.567(1)°, β = 97.779(1)°, γ = 91.504(1)°, V = 1070.90(3) Å3, Z = 2, R gt(F) = 0.0382, wR ref(F 2) = 0.1083, T = 193 K.